Trend and decomposition analysis of risk factors of childbirths with no one present in Nigeria, 1990–2018 (2021)
Objectives To assess the trend and decompose the determinants of delivery with no one present (NOP) at birth with an in-depth subnational analysis in Nigeria. Design Cross-sectional.Setting Nigeria, with five waves of nationally representative data in 1990, 2003, 2008, 2013 and 2018. Participants Women with at least one childbirth within 5 years preceding each wave of data collection. Primary and secondary outcome measures The outcome of interest is giving birth with NOP at delivery defined as childbirth assisted by no one. Data were analysed using Χ2 and multivariate decomposition analyses at a 5% significance level. Results The prevalence of having NOP at delivery was 15% over the studied period, ranges from 27% in 1990 to 11% in 2018. Overall, the prevalence of having NOP at delivery reduced significantly by 35% and 61% within 2003–2018 and 1990–2018, respectively (p<0.001). We found wide variations in NOP across the states in Nigeria. The highest NOP practice was in Zamfara (44%), Kano (40%) and Katsina (35%); while the practice was 0.1% in Bayelsa, 0.8% in Enugu, 0.9% in Osun and 1.1% in Imo state. The decomposition analysis of the changes in having NOP at delivery showed that 85.4% and 14.6% were due to differences in women’s characteristics (endowment) and effects (coefficient), respectively. The most significant contributions to the changes were the decision-maker of healthcare utilisation (49%) and women educational status (24%). Only Gombe experienced a significant increase (p<0.05) in the level of having NOP between 2003 and 2018. Conclusion A long-term decreasing secular trend of NOP at delivery was found in Nigeria. NOP is more prevalent in the northern states than in the south. Achieving zero prevalence of NOP at delivery in Nigeria would require a special focus on healthcare utilisation, enhancing maternal education and healthcare utilisation decision-making power.